Nordic Exceptionalism? How Scandinavian Border and Coast Guards Rationalize Their Participation in Frontex Operations - Eline Waerp (Nordic Journal of Migration Research)
This paper examines how Scandinavian border and coast guards seconded to Frontex operations understand their participation in them. Drawing on interviews with Swedish and Danish border and coast guards, the paper introduces the notion of Nordic exceptionalism in order to explain how they view their contribution to Frontex operations as positive for Frontex, other member states, and refugees and migrants themselves. Nordic exceptionalism refers to the interviewees’ perception of higher moral standards and stronger work ethic in the Nordic countries vis-à-vis in the Southern, Central, and Eastern European countries. The paper explores how the Scandinavian border and coast guards’ belief that refugees and migrants would be worse off if they were not present at sea rationalizes their participation in Frontex operations, despite their concerns regarding poor fundamental rights protections. Advancing the notion of banal securitization, the paper argues that although the Scandinavian border and coast guards discursively resist the criminalization of migration, they acquiesce to its securitization through their continued participation in Frontex operations. Nordic exceptionalism thus facilitates the banal securitization of migration by inoculating the interviewees from the harmful consequences of their work.